Reconstructing The Concept of Superhero in Ms. Marvel TV Series: First Female Moslem Superhero’s Journey - Viani Alifa Almas (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2022)
Marvel Studios is the most successful franchise when it comes to superhero movies, their list of superheroes that represents “the best of humankind” goes on and on, however when it comes to showing how diverse humanity actually is they have not done their best, at least until their take on Ms. Marvel. Ms Marvel series shows the rise of Kamala Khan, the first American-Pakistani Muslim teenage superheroes amidst the typically male dominated roles, this less than usual take inspire the creation of this research that aims to examine how to deconstruct and reconstruct Muslim female superheroes in Muslim minority places. In this study, researchers used a deconstruction approach in analyzing Ms. Marvel (2022) as source that leads to forms of deconstruction and reconstruction of the Muslim female superhero concept. This research found there are forms of efforts to deconstruct the Muslim female superhero concept in Ms. Marvel of the issue of white supremacists and immigrant Muslims, because the main character of the series takes the point of view of a Muslim woman who is a minority in America. The effort to deconstruct the concept of a Muslim female superhero is an attempt to undermine the concept of a classic superhero, which Kamala herself has succeeded in deconstructing. However, there is a dualism as in Kamala's position as a Muslim woman, she is not completely free because she is still shackled by the patriarchal cultural system. The existence of ambivalence in this deconstruction effort eventually highlights the previous concept. The aim of deconstructing this series is to rebuild Kamala Khan's Muslim superhero concept. Kamala managed to become a superhero thanks to her hard work, even though she had to face difficult tasks.